UPAYA PENDIDIKAN KELUARGA DALAM MENANGGULANGI KENAKALAN REMAJA DI DESA DAUN SANGKAPURA BAWEAN GRESIK - Ansharuddin M (CENDEKIA: Jurnal Studi Keislaman, 2018)
This article will discuss family education and family efforts to overcome juvenile delinquency. The family as the first and foremost educator for children is obligatory to educate children to be good. The rise of the phenomenon of juvenile delinquency is increasingly troubling the public, especially in the era of globalization and technology and in the middle of school politics which increasingly corners the existence of family education. For this reason, this study seeks to uncover and analyze the forms of juvenile delinquency and how the family's efforts in overcoming juvenile delinquency are increasingly prevalent, especially in the midst of the Bawean people who are 100% Muslim. Therefore, the existence of this research can later be used as input for all families to look after and care for their children as well as possible so that they can become good children.